Accountability for Village Fund Allocation Management in the Administration of Sambong Village, Ngasem District, Bojonegoro Regency - Yakin, Moch. Ainul; Nugroho, Mahendra Adhi (EAJ (Economic and Accounting Journal), 2023)
This study aims to determine the accountability of village fund allocation, known as ADD management, in Sambong Village, Ngasem District, Bojonegoro Regency, to realize good governance. Then it was intended to know and explain the planning system and the joint implementation of the responsible management system for managing the Allocation of Regional Funds (ADD) in Samboing Village, Ngaseim District, Kabuipateiin Boijoigoiroi. Furthermore, to know how far the accountability of ADD management will affect the accountability of ADD management in improving social welfare happened. This research technique uses qualitative descriptive research methods. in the form of written or spoken words from people and informant who can provide direct information that research requires. The results of this study were under applicable regulations. The planning stage begins with holding hamlet meetings and involving the local community. However, the activeness of Village Institutions could have been more enthusiastic in the process of ADD activities when conducting Musrenbangdes. The stages of implementing ADD management were carried out by an implementing team that was trusted to manage the activities to be carried out, and the budget used was announced by installing information boards; however, to realize good governance, village staff had difficulty finding workers and were afraid of protests from some village communities. The accountability stage of ADD management uses various types of reports, and the difficulty level is accountability for the ADD management process, namely, rules that are easy to change. However, this is relatively easy because it creates new challenges that can be used as a basis for learning to improve productivity and performance in ADD management to realize good governance.